A representação do incondicionado na crítica da razão pura - Coriolano, Ericsson Venâncio (2016)
The main theme of this PhD thesis is the representation of the unconditioned in the Critique of Pure Reason. It is argued an essential function of the unconditioned for the preparation of logical and transcendental activities of speculative reason. There is in this work, in a new light, the defense of exposition of some theses about the following sub-themes: 1) the origin of transcendent concepts necessary mode in consciousness; 2) the definition of transcendental appearance; 3) the development and solution of the antinomy of pure reason; 4) the definition of transcendental freedom; 5) the exposition of the function of speculative reason in the establishment of scientific knowledge. Themes (1) and (2) are covered in the first chapter through the exposition of the function of representation of the unconditioned in the development of subjective derivation of transcendental ideas carried out by Kant, of A293/B349 to A338/B396, in the Critique of Pure Reason. Themes (3) and (4) are treated in the second chapter, specifically in the presentation of the results of the research about The Antinomy of Pure Reason, in the second chapter of the second book of the Transcendental Dialectic, of A405/B432 to A568/B596. The theme (5) is found in the third chapter and it is presented by the defense of the thesis that the speculative reason has a vital role to scientific knowledge, it is obtained from the study about Appendix of the Transcendental Dialectic, of A642 / B670 to A705 / B733. It is defended here, ultimately, that all these issues are based on a fundamental thesis that permeates all Transcendental Dialectic, namely that the unconditioned can be determined as a transcendental element with a regulative empirical use of all experience to establish a systematic unity of all objective knowledge.